Generative Design Research for a Culturally Sensitive Subject: Exploring Menstrual Practices and Product Experiences to Inspire Design - Efilti, Pelin; Timur, Şebnem (Design and culture, 2025)
The intimate nature of menstruation and the taboos surrounding it cause numerous challenges for conducting research in this field. To explore menstrual practices and product experiences, in this study, a generative workshop study was designed with participatory research tools and co-design exercises, following a semi-structured interview schedule. The generative research was seen as having the potential to overcome the intimate nature of the research subject and to gather design insights for menstruation. The workshop sessions include physical and visual research tools and generative exercises that are deliberately thought to remind the participants of the context of use, evoke dialog, and inspire new ideas. Understanding the underlying complexities and motives behind menstruation is crucial for the development of better solutions, products, and/or services. The data obtained from the workshops were analyzed to reveal design criteria for menstruation products and experiences by following the procedures of grounded theory. "Failures," "limitations," "social codes," "tactics," and "improvements" have been identified and discussed as design criteria that could inspire designers.